2010
DOI: 10.1038/mi.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 defines a novel immune pathway of antifungal resistance

Abstract: The role of IL-17 and Th17 cells in immunity vs. pathology associated with the human commensal Candida albicans remains controversial. Both positive and negative effects on immune resistance have been attributed to IL-17/Th17 in experimental candidiasis. In this study, we provide evidence that IL-22, which is also produced by Th17 cells, has a critical, first-line defense in candidiasis by controlling the growth of infecting yeasts as well as by contributing to the host's epithelial integrity in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
211
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(225 citation statements)
references
References 52 publications
10
211
0
Order By: Relevance
“…In line with what is observed in humans 7 , Candida overgrowth occurs under conditions of defective interleukin (IL)-17F 8 or IL-17RA signalling [8][9][10] , which suggests the importance of IL-17RA signalling in preventing infection. Under specific circumstances, IL-17A may, in fact, contribute to disease susceptibility in a host-autonomous fashion, perhaps by modifying the intrinsic virulence of the fungus 8 . In this study, we provide molecular evidence that fungal pathogens may exploit, via a conserved family of glycosylphosphatidylinositol (GPI)-anchored crosslinking proteins, host immunity mediatorsspecifically, IL-17A-for adaptation, not necessarily implicating virulence, and pathogenesis in mammalian hosts.…”
supporting
confidence: 62%
“…In line with what is observed in humans 7 , Candida overgrowth occurs under conditions of defective interleukin (IL)-17F 8 or IL-17RA signalling [8][9][10] , which suggests the importance of IL-17RA signalling in preventing infection. Under specific circumstances, IL-17A may, in fact, contribute to disease susceptibility in a host-autonomous fashion, perhaps by modifying the intrinsic virulence of the fungus 8 . In this study, we provide molecular evidence that fungal pathogens may exploit, via a conserved family of glycosylphosphatidylinositol (GPI)-anchored crosslinking proteins, host immunity mediatorsspecifically, IL-17A-for adaptation, not necessarily implicating virulence, and pathogenesis in mammalian hosts.…”
supporting
confidence: 62%
“…In studies of Candida albicans vaginitis, the S100 antimicrobial peptides have been examined, and data have shown that their role is more important in neutrophil recruitment than in direct microbicidal activity against Candida (Johnston et al, 2013;Yano et al, 2010Yano et al, , 2012a. However, additional studies by other laboratories have shown that IL-22 is critical to protection in a vaginal model of Candida albicans infection (De Luca et al, 2010. Furthermore, our in vitro studies did not show anti-fungal activity of any of the purified AMPs against C. neoformans (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…After birth, the key role of IL-22 in intestinal homeostasis and defense, and more generally in mucosal immunity, is well documented 10,12,13 . It may therefore not come as a surprise that the immune system has evolved a constitutive pathway for the production of IL-22.…”
Section: Discussionmentioning
confidence: 99%
“…We now show that RORγt + ILCs produce most of intestinal IL-22 at steady state and markedly increase this activity during inflammation. RORγt + ILCs therefore play a critical role in intestinal homeostasis and defense, as IL-22 induces the production of anti-bacterial peptides by epithelial cells, is required for intestinal defense against bacterial and fungal pathogens [8][9][10]12,13 and is involved in protection of intestinal tissues from the effects of pathological inflammation, presumably through the induction of anti-apoptotic factors 15, 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation